Internationalization in Isolation: COVID-19 Implications - Crăciun , Daniela; de Gayardon, Ariane (International Higher Education, 2021)
When a global health crisis renders mobility impossible, making all universities de facto isolated and remote, researchers should look at ways to redefine and generalize internationalization while removing the exclusive focus on mobility. Learning from the “unusual suspects” of internationalization—i.e., institutions that were considered remote before the crisis—is a unique opportunity to move the focus away from student mobility and foster more sustainable and inclusive internationalization practices.